Organic food supply chain – the case in Macedonia - Sekovska, Blagica (Economics of Agriculture, 2010)
The organic sub-sector in Macedonia follows an industrial model of agriculture and its development is mostly based on expectations of market price premiums. The organic farming community is very small and at the very beginning of the learning curve. In these circumstances supply is seen as the biggest problem of developing a market. The research involved analysis of consumers perceptions and needs of organic agriculture, also. It focused more closely on potential for export market development, but based on opportunity of developing a domestic market. Farmers are not ready for export yet and any potential initiative should be taken with organization of collective capacities. The success of any endeavour highly depends on the increase of transparency within the organic community. Development of the domestic market should be given more priority at this point as it has more chances of short term success and would serve as a foundation for eventually accessing an export market. Main focus in this paper is put on organic supply chain in Macedonia and preferences of domestic consumers about demand of domestic organic products.